La transformation des territoires nordiques urbanisés : Étude de la forme et des traits distinctifs des villages inuit du Nunavik - Rochette, Maxime (Études Inuit Studies, 2020)
This article looks at the shape of the built environment of the Inuit villages of Nunavik that results from a relatively recent urbanization process. It seeks to understand how the built environment of these villages has been transformed, in time and space, from their foundation to the present day. How have these environments adapted to the territorial and climatic constraints and to the cultural aspirations of their inhabitants? Using maps, aerial photographies, development plans, texts relating the occupation of the territory and historical and recent photographies, the author makes a morphological analysis of the 14 Inuit villages, i.e. a characterization of the current landscape and built forms. Different variables of formal, dimensional, use and relative position are examined to reveal three types of settlements with variants: clustered, linear and block settlements. The morphogenesis of the villages of Kuujjuaq and Inukjuak, two key types, helps to characterize and understand the evolution of the shape of these settlements over time. Considering historical, political and cultural factors, this part of the analysis brings out structures of permanence and symbolic markers. The article concludes with a discussion on the relevance of typomorphology as a method of reading northern and indigenous built environments and urban development in an Inuit context. Cet article s’intéresse à la forme de l’environnement bâti des villages inuit du Nunavik qui résulte d’un processus d’urbanisation relativement récent. Il s’agit de comprendre comment le cadre bâti de ces villages s’est transformé, dans le temps et dans l’espace, depuis leur fondation jusqu’à aujourd’hui. Comment ces environnements se sont-ils adaptés aux contraintes territoriales, climatiques et aux aspirations culturelles de ses habitants ? À partir de cartes géographiques, de photographies aériennes, de plans d’aménagement, de textes relatant l’occupation du territoire et de photographies historiques et récentes, l’auteur fait l’analyse morphologique des ...